Complexos anfifílicos de antimônio(V) e composições de fármacos à base de antimônio com ciclodextrina: síntese, caracterização físico-química e potencial terapêutico - Weverson Alves Ferreira (2010)
Leishmaniases are diseases that can produce cutaneous,mucocutaneous or visceral clinical manifestations. The World HealthOrganization (WHO) included this disease among the six most importantendemic diseases in the World, because of its high incidence. The pentavalent antimonials are the first-line drugs used in the treatment of leishmaniasis, however, their toxicity and prolonged parenteral administration limit their clinical use. This thesis presents new formulations for the classical pentavalent antimonials, meglumine antimonate (MA) and sodium stibogluconate (SSG), with -cyclodextrin (-CD) and a new amphiphilic antimony series. These compounds and formulations have been designed to promote the absorption of Sb by the oral route. The SSG, evaluated by elemental analysis, thermal analysis, IR, osmolarity measurements and ESI-MS, showed 1:1, 1:2, 2:2 and 2:3 Sb(V)-ligand complexes. The novel structures proposed for this drug may help to understand its pharmacological properties. Preliminary assays were performed in Swiss mice with SSG and it SSG:-CD 1:1 composition to evaluate the influence of -CD on the absorption of Sb by oral route. A (non-conventional) composition MA:-CD was prepared at 7:1 molar ratio and characterized by thermal analysis, IR, 1H RMN and light scattering spectroscopy. The novel composition was found to act as a sustained drug release system and to promote greater and more prolonged plasma levels of Sb when compared to MA, after administration to Beagle dogs by oral route. This work presents a new modality of release system, based on the Sb-O-(-CD)interaction. Amphiphilic pentavalent antimonials were obtained with the ligands octanoyl N-methyl-glucamide, decanoyl N-methyl-glucamide and dodecanoyl N methyl-glucamide and, when evaluated by elemental analysis, IR, circular dichroism, 1H RMN and ESI-MS, revealed the formation of 1:3 Sb(V)-ligand complexes. The preliminary tests of these compounds carried out in Swiss mice, with the aim of evaluating the impact on the absorption of Sb by the oral route, showed very promising results. The amphiphilic character of these new antimonials allows us to propose for the first time innovative antimony-based formulations for the topical treatment of cutaneous leishmaniasis.